Diane Arbus's 1960s : auguries of experience - Gross, Frederick (University of Minnesota Press, 2012)
In any decade the work of only a very few artists offers a template for understanding the culture and ideas of their time. Photographer Diane Arbus is one of these rare artists, and this book returns Arbus's work to the moment in which it was produced and first viewed to reveal its broader significance for analysing and mapping the culture of the 1960s. While providing a unique view of the social, literary, and artistic context within which Arbus worked, this book also measures the true breadth and complexity of her achievement.